The Role Of Micro Waqf Banks In Strengthening The Halal Industry Ecosystem Through Pesantren-Based MSME Empowerment: A Case Study Of Nurul Huda Micro Waqf Bank - Zulfikri (International Journal of Management and Business Economics, 2025)
This study aims to analyze the role of the Nurul Huda Micro Waqf Bank (BWM) in empowering Micro, Small, and Medium Enterprises (MSMEs) and supporting the development of the halal industry in South Sumatra. The research employed a qualitative method with an empirical approach through observation, interviews, and documentation. The findings reveal that the Nurul Huda Micro Waqf Bank functions as a financing institution without engaging in fundraising activities, targeting productive low- to middle-income communities located around the Islamic boarding school. The institution's funding originates from a Corporate Social Responsibility (CSR) grant provided by Bank Sumsel Babel Syariah amounting to IDR 5 billion, of which IDR 1 billion is allocated for financing activities and IDR 4 billion is designated as an endowment fund to support operational sustainability. Through financing programs based on the qardh contract and continuous mentoring conducted through the Weekly Halaqah (HALMI) program, the institution has successfully contributed to increased business production and higher customer income. Furthermore, the mentoring activities have encouraged MSME actors to obtain halal certification, thereby supporting the development of the halal industry. This study concludes that the Nurul Huda Micro Waqf Bank plays a significant role in expanding access to financing, empowering MSMEs, and strengthening the pesantren-based halal industry ecosystem.